Good Governance Strategy in Determining The Quality of Public Services in Sukabumi City - Muhammad Iqbal Inayatullah (Institute of Computer Science (IOCS), 2021)
Service innovation in the city of Sukabumi must be improved in order to get a WTP (Wajat Without Exception) rating. Good governance strategies are needed to improve public services that provide innovation and convenience for the community, because in fact the policies of public sector organizations can be measured by service quality. The research method is a literature study while the qualitative approach. The results of the study The strategic role of the bureaucracy in carrying out its duties and functions in determining good public services as discussed above, it can be concluded that the role of the bureaucracy does not only rely on the ability to carry out public services or fulfill the needs of public goods and services, but also as a motivator for the growth and development of participation. community in meeting the needs of the community itself.